Cardiovascular magnetic resonance imaging in hypertrophic cardiomyopathy: the importance of clinical context. (22nd December 2017) - Quarta, Giovanni; Aquaro, Giovanni Donato; Pedrotti, Patrizia; Pontone, Gianluca; Dellegrottaglie, Santo; Iacovoni, Attilio; Brambilla, Paolo; Pradella, Silvia; Todiere, Giancarlo; Rigo, Fausto; Bucciarelli-Ducci, Chiara; Limongelli, Giuseppe; et al.
Abstract: In patients with suspected or established hypertrophic cardiomyopathy (HCM), cardiovascular magnetic resonance (CMR) is widely employed for clinical management, given its multimodality approach capable of providing unique information on cardiac morphology, function, and tissue characterization. Guidance regarding all aspects of HCM diagnosis and management is provided by the comprehensive 2014 European Society of Cardiology (ESC) guidelines on HCM. CMR should be performed in centres with recognized expertise in heart muscle diseases, by physicians who are familiar with the whole HCM disease spectrum, differential diagnoses, and pitfalls. Because CMR is usually performed and interpreted by physicians not directly involved in patient care, detailed, bidirectional, and standardized communication becomes essential to obtain best results and avoid misinterpretation. In order to maximize the potential of CMR, it is of paramount importance that reporting physicians are provided with the essential clinical information and that, in turn, referring physicians are given a core set of CMR morphological, functional, and tissue characterization results following the test. This article aims to summarize the current knowledge on the role of CMR in managing HCM and, in addition, to review the importance of the clinical context in which the report is provided, in both adult and paediatric population, highlighting implications for clinical research.